Targeted neocortical cell death in adult mice guides migration and differentiation of transplanted embryonic neurons - Sheen, VL (J Neurosci, 1995)
Local expression of cellular and molecular signals is required for normal neuronal migration and differentiation during neocortical development and during periods of plasticity in the adult brain. We have previously shown that neonatal and juvenile mice that induction of apoptotic degeneration in neocortical pyramidal neurons by targeted photolysis provides an altered environment that directs migration and differentiation of transplanted embryonic neurons. Here we employ the same paradigm in adult mice to test whether targeted photolysis induces the reexpression in the mature brain of developmental signals that control migration, differentiation and integration of embryonic neurons. We examined both the time course of migration and the morphologic and immunocytochemical differentiation of embryonic neurons transplanted into regions of targeted photolytic cell death. Pyramidal neurons in neocortical lamina II/III underwent photolytically induced apoptosis after retrograde incorporation of the photoactive chromophore chlorine e6 and transdural exposure to 674 nm near-infrared laser energy. Embryonic day 17 neocortical neurons were prelabeled with fluorescent nanospheres and the lipophilic dye PKH26, transplanted into regions of ongoing neuronal degeneration in adult mice, and examined histologically and immunocytochemically. Transplanted neurons began migration into regions of neuronal death within 3 d and differentiated into large pyramidal neurons similar to those degenerating. In contrast, neurons transplanted into intact cortex did not migrate, and they differentiate into small presumptive interneurons. Migration up to 430 microM in experimental mice was complete by 2 weeks; approximately 45% of the donor neurons migrated greater than 3 SDs beyond the mean for neurons transplanted into intact neocortex of age-matched adult hosts. Following migration, dendrites and axons of many donor neurons were properly oriented toward the pial surface and corpus callosum, indicating integration into the host parenchyma. Neurofilament and neuron-specific enolase staining further support appropriate differentiation and integration. These results indicate that signals guiding neuronal migration and differentiation in neocortex are reexpressed in adult mice well beyond the period of corticogenesis within regions of targeted photolytic cell death. Elucidating the molecular mechanisms underlying these events by comparison with adjacent unperturbed regions will contribute to efforts toward future therapeutic transplantation and control over endogenous plasticity.